Risk control system construction of China’s equity crowdfunding platforms: A comparative study on the differences between equity crowdfunding and traditional venture capital investment - BAI, Wentao (Institutional Knowledge at Singapore Management University, 2020)
Equity crowdfunding is a new type of public financing activity realized by Internet technology with small single investments funds, which is different from traditional venture capital. It greatly solves the equity investment problem of middle-class people and the difficulties of small and medium-sized enterprises and start-ups in financing. It is also conducive to the construction of multi-level capital market, and the healthy development of national financial system. Due to the advantages of equity crowdfunding, the global equity crowdfunding market has developed rapidly in recent years. Unfortunately, China's formal legislation on equity crowdfunding has not been introduced yet. Each platform can only exist in the form of a crowdfunding-alike equity investment platform, and most of them have been developing savagely with no effective risk control system established at all. Investment failure occurs frequently and investors suffer huge losses. The risk control system in this paper targets at the investment loss risk faced by equity crowdfunding investors due to non-systematic causes. The construction of the risk control system proposed here include not only the narrow-scale risk control at the project level, but also the various aspects of the overall business process of the platform. This paper first reviews the literature and regulatory practices in the field of equity crowdfunding. Scholars have conducted researches on equity crowdfunding mainly from the perspectives of the participating parties’ behavior motivation, factors affecting the success of financing, risks of equity crowdfunding and countermeasures to deal with the risks. In terms of risk countermeasures, most scholars hope to reduce the risks by improving relevant laws and regulations at the national level and strengthening supervision by relevant national departments. At present, global regulatory practices of equity crowdfunding reflect the considerations of promoting capital formation, improving financing efficiency and balancing investor protection. In general, one way is to protect investors through the investor suitability and the investment cap; the second way is to ensure equity crowdfunding platforms to play the role of credit intermediary to prevent risks. After that, this paper focuses on the analysis of causes of equity crowdfunding risks in China, which include the characteristics of the financing parties, the characteristics of investors, information asymmetry, principal-agent conflicts, and the platforms’ excessive pursuit of short-term interests. In view of the causes of equity crowdfunding risks, this paper analyzes and compares the similarities and differences between equity crowdfunding and traditional venture capital. Focusing on the significant differences between the two in terms of business model, positioning, investor endowment, and investor diversification abilities, this paper then proposes corresponding risk control measures and the overall construction of risk control system of China’s equity crowdfunding platforms dividing into five aspects including risk control before the launch of the project, risk control in fundraising, risk control of post-investment, investor management and education, and platform team building and incentives. To make the risk control system operable, this paper proposes specific models to illustrate how to evaluate project risk and investor risk preference and tolerance. In terms of project risk assessment and classification, this paper proposes the method of combining Analytic Hierarchy Process and Fuzzy Comprehensive Evaluation to make the assessment process more accurate and scientific. In terms of investor risk preference and tolerance evaluation, a questionnaire is used to better understand investors, and the optimal scale method is used to regress the questionnaire data. It is found that age, education level, family annual disposable income is significantly related to investors' risk preference and tolerance. Subsequently, a case study of the risk control system is conducted with real investment cases on one domestic platform. It is found that the risk control measures proposed in this paper better reveal the project risks, and are more advantageous for making judgment regarding the project and protecting the interest of investors. Finally, on the basis of summary, the prospect of future research is proposed, hoping to better verify the effectiveness of the risk control system through continuous follow-up research and investigation.